2011
DOI: 10.1093/sleep/34.1.39
|View full text |Cite
|
Sign up to set email alerts
|

Behavioral and Genetic Dissection of a Mouse Model for Advanced Sleep Phase Syndrome

Abstract: CAST mice have an advanced activity phase similar to human advanced sleep phase syndrome. This advanced phase is not due to its shorter period length or smaller light-induced phase shifts, but appears to be related to both light masking and altered coupling of the circadian pacemaker with various outputs. Lastly, a QTL influencing this trait was confirmed and narrowed using congenic mice as a first step toward gene identification.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
13
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(15 citation statements)
references
References 43 publications
2
13
0
Order By: Relevance
“…Mice were placed in the piezoelectric floor monitoring chamber to assess activity over a five-day period. Overall, we found strain differences in relation to activity traces that may be reflective of previously reported differences in circadian rhythm and entrainment to light [21]. Female percent hourly inactivity was averaged across animals and strains starting at midnight of the first day.…”
Section: Supporting Informationsupporting
confidence: 68%
See 1 more Smart Citation
“…Mice were placed in the piezoelectric floor monitoring chamber to assess activity over a five-day period. Overall, we found strain differences in relation to activity traces that may be reflective of previously reported differences in circadian rhythm and entrainment to light [21]. Female percent hourly inactivity was averaged across animals and strains starting at midnight of the first day.…”
Section: Supporting Informationsupporting
confidence: 68%
“…Importantly, the genetic variation encompassed in these strains and interactions of different gene networks evolved, thus, are likely physiologically relevant to the natural world. This variation includes genes previously associated with AD including Apoe , Trem2 and Tyrobp , and these strains also show variation in phenotypes relevant to AD risk factors including cardiovascular health [16], insulin secretion [1719], gut microbiota [19, 20] and circadian rhythm [21].…”
Section: Introductionmentioning
confidence: 99%
“…Similar to the period in fibroblast cultures, the periods of behavioral rhythms in CAST/EiJ mice were shorter than those in A/J and C57BL/6J mice. Our observation is entirely consistent with other studies that have reported shorter rhythm periods in male CAST/EiJ compared to C57BL/6J mice 34 . Shorter periods in CAST/EiJ mice were further supported by a more recent study which demonstrated strain-dependent differences in circadian wheel-running behavior 6 .…”
Section: Discussionsupporting
confidence: 93%
“…While a number of genetic and molecular studies have sought to determine mRNA expression profiles which correlate with sleep/wake state, such approaches have not focused on the determination of the underlying genes that regulate specific sleep-wake states (Thompson et al, 2010; Mackiewicz et al, 2009; Cirelli et al, 2004; Mackiewicz et al, 2007). More recently, genome-wide studies in humans and model organisms have been carried out in order to identify genes which underlie the regulation of sleepwake traits (Millstein et al, 2011; Sehgal & Mignot, 2011; Winrow et al, 2009; Jiang et al, 2011; Miyagawa et al, 2008). …”
Section: Introductionmentioning
confidence: 99%